A Hybrid Parallel Numerical Algorithm for Three-Dimensional Phase Field Modeling of Crystal Growth - Strachota, Pavel; Beneš, Michal (Proceedings of the Conference Algoritmy, 2016)
We introduce a hybrid parallel numerical algorithm for solving the phase field formulation of the anisotropic crystal growth during solidification. The implementation is based on the MPI and OpenMP standards. The algorithm has undergone a number of efficiency measurements and parallel profiling scenarios. We compare the results for several variants of the algorithm and decide on the most efficient solution.